Dietary Acid-Binding Capacity-4 Influences Nursery Pig Performance and Fecal Dry Matter - Ethan B. Stas; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 360 pigs (200 × 400 DNA; initially 12.9 lb) were used to evaluate the impact of increasing the acid-binding capacity-4 (ABC-4) of the diet on nursery pig performance and fecal dry matter (DM). At weaning, pigs were allotted to 1 of 6 dietary treatments. There were 5 pigs per pen and 12 replications per treatment. Pigs were fed experimental diets in two phases with phase 1 being from d 0 to 10 post-weaning followed by phase 2 from d 10 to 23. Diets were formulated with increasing ABC-4 levels ranging from 150 meq/kg (diet 1, low ABC-4) to 312 meq/kg (diet 5, high ABC-4) in phase 1 and 200 meq/kg (diet 1, low ABC-4) to 343 meq/kg (diet 5, high ABC-4) in phase 2. For diet 1, the low ABC-4 diets were formulated using specialty soy protein concentrate (AX3 Digest; Protekta; Newport Beach, CA) at 12.50 and 10.00% of the diet in phase 1 and 2, respectively. The low ABC-4 diet also utilized fumaric acid and formic acid at 0.50 and 0.48% of the diet, respectively for both phase 1 and 2. For diets 2 (medium low), 3 (medium), 4 (medium high), and 5 (high), increasing ABC-4 of the diet was achieved by progressively decreasing the level of acidifiers and replacing specialty soy protein concentrate with enzymatically treated soybean meal (HP 300; Hamlet Protein; Findlay, OH) on an SID Lys basis. Diets 1 through 5 were formulated without the inclusion of ZnO. For diet 6, a positive control diet was utilized which had the same formulation as the highest ABC-4 diet but with the addition of pharmacological levels of Zn from ZnO. Following phase 2, all pigs were placed on a common diet until d 38 of the study. In the experimental period (d 0 to 23) and overall (d 0 to 38), a quadratic response was observed (P≤ 0.030) where BW and ADG were highest for pigs fed the medium low and medium ABC-4 diets. During the experimental period (d 0 to 23), pigs fed increasing ABC-4 levels had poorer (linear,P= 0.002) F/G. For overall F/G, a quadratic response was observed (P= 0.023) where F/G was most improved for pigs fed the medium low and medium ABC-4 levels. Pigs fed diets with ZnO had increased (P≤ 0.038) ADG compared to pigs fed diets without ZnO during the experimental period and overall. In summary, pharmacological levels of Zn improved nursery pig performance as expected. The medium low and medium ABC-4 levels improved performance compared to higher ABC-4 levels, suggesting an optimal ABC-4 level of the diet for this study would be at or below 256 and 295 meq/kg in phase 1 and 2, respectively.
Keywords: acid-binding capacity; nursery pig; fecal dry matter